Analisis Hubungan Faktor Lingkungan Terhadap Kejadian Penyakit Kulit Pada Masyarakat yang Tinggal di Aliran Sungai Indragiri di Desa Sukaping Kecamatan Pangean - Ardilah Rahmadani; Ridwan Manda Putra; Zahtamal Zahtamal (SEHATI: Jurnal Kesehatan, 2023)
Skin disease is a disease relate to environment and human behavior. Environmental factors are closely relate to skin diseases such as clean water facilities, accupancy density, economic factors, and sosial factors. This reasearch method used in Analytical survey method with a cross-sectional research design. The sample in this study was 87 people. The sampling technique used Simple Random Sampling. The analysis method used is univariate analysis, bivariate analysis with the chi square test using the SPSS program and multivariate analysis. The results of multivariate analysis found that there were 3 risk factors with the gratest influence of contribution to the incidence of skin diseases, namely clean water facilities OR (0,508), the habit of washing hand with the soap OR (0,204), and economic factors OR (0,203)